دور نُظم المعلومات التسويقيَّة في ترشيد القرارات الإداريَّة في المُنشآت الزراعيَّة في السَّاحل السُّوري - جحجاح, محسن; عليو, محمود; زرقة, أبو العلاء (Latakia University Journal -Biological Sciences Series, 2016)
هدف البحث إلى بيان، وتحليل، دور نُظم المعلومات التسويقيَّة في إنتاج المعلومات التسويقيَّة ذات الكفاءة والفعاليَّة للوفاء بالاحتياجات الإداريَّة اللازمة لترشيد القرارات الإداريَّة في المنشآت الزراعيَّة في الساحل السوري.ولتحقيق أهداف البحث، والإجابة على تساؤلاته، اعتُمد في جمع البيانات المُتعلقة بالمُوضوع على الأدبيَّات والدراسات السَّابقة ذات الصلة، أمَّا الإطار العملي فقد اعتُمد على إعداد استبيان تمَّ تصميمه لهذا الغرض، وقام الباحث بإجراء التحليلات اللازمة واختبار فرضيَّات البحث، وتوصَّل إلى مجموعة من الاستنتاجات والتوصيات، أهمها: • وجود بعض مظاهر الانخفاض في وضع أدلة فعَّالة لتحديد طرق إثبات ومُعالجة المعلومات، مما يتطلَّب اهتمَّام الإدارة بتوفير المقومات اللازمة لتشغيل نظام المعلومات التسويقي بكفاءة وفعاليَّة.• تدني فعاليَّة استخدام نُظم المعلومات التسويقيَّة في عمليات التخطيط، وترجمة الأهداف، ووضع السياسات للمُنشآت، ممَّا يستدعي ضرورة الاهتمَّام بتوفير المعلومات اللازمة للتخطيط والرقابة واتخاذ القرارات الرشيدة.• الانخفاض في إجراء التحليلات اللازمة لعناصر البيئة المُحيطة ممَّا يُؤثر على نوعيَّة القرارات التي يتمَّ اتخاذها، وهذا يستوجب الاهتمَّام بالعوامل المُحيطة بالمُنشأة عند إعداد وتطوير نُظم المعلومات التسويقيَّة، وذلك لضمان تحقيق كفاءة وفعاليَّة هذه النُظم.• مازال الاهتمام ببناء نظم المعلومات التسويقية من قبل المنشآت الزراعية محدوداً.This study aimed to analyze the role of a statement and marketing information systems in the production of efficient and effective marketing information necessary to meet the administrative needs of the rationalization of administrative decisions in agricultural facilities in the Syrian coast.To achieve the objectives of the study and answer its questions, we relied on data relevant to the literature and previous relevant studies related to the collection, and the operational framework we have adopted in the preparation of a questionnaire designed for this purpose, and the researcher to conduct the necessary analysis and test hypotheses, and arrive at a set of findings and recommendations:• The existence of some aspects of the decline in the development of effective evidence to identify ways to prove and information processing, which requires management attention to providing the necessary ingredients for the operation of the marketing information system efficiently and effectively.• Low effective use of marketing information systems in the planning and translate the goals and policy-making facilities, which calls for the need for attention to providing the necessary planning and control of information and decision-making governance.• decline in conducting the necessary analysis of the components of the surrounding environment, which affects the quality of decisions taken, and it requires attention to factors surrounding the facility in the preparation and development of marketing information systems, so as to ensure the efficiency and effectiveness of these systems.• The study showed that there is limited attention by agricultural enterprises for the construction of marketing information systems.